A lossless parallel data compression method using threads - Islam, Md. Rafiqul; Arifin, Md. Shamsul; Md. Sap, Mohd. Noor; Md. Shams Tibrizet, Kazi (Penerbit UTM Press, 2005)
The performance of lossless data compression depends mainly on compression rate and compression time. The compression time of maximum of the existing sequential compression algorithms can be reduced using the conception of parallel compression. In this paper, we have proposed a method for data compression, which significantly reduces the compression time. We used Burrows-Wheeler Inversion Coding (BWIC) algorithm and threads in the proposed method. Here, we describe stages of BWIC algorithm and show the efficiency of the runtime of the proposed method over BWIC experimentally.